The Excretion of BRCAA Antibody-Conjugated Gold Nanoclusters from Kidneys of Treated Rats - Kunlu Liu; Haixia Li; Yajun Wu; Chunlei Zhang; Duanyun Si; Quansheng Li; Sa Zhang; Jiye Yin; Yuanyuan Liu; Wensheng Qu; Junhua Wu; Yingge Zhang; et al. (Nano Biomedicine and Engineering, 2017)
The gold nanoclusters (Au-NCs) have emerged for delivery of various payloads such as small molecular drug and big molecular proteins due to their low immunogenicity, quick clearance and good biocompatibility. Even though they have shown great prospective in biomedical area, there are also some security problems which should be investigated further more. BRCAA1 mAb Au-NCs is a probe for gastric cancer diagnosis prepared by conjugating BRCAA1 monoclonal antibody with fluorescent Au-NCs. In this research, the renal excretion and effect on glomerulus filtration of BRCAA1 mAb AuNCs in rats were investigated. The result indicated that BRCAA1 mAb Au-NCs could be eliminated through the glomerulus filtration as early as 2 hr after the administration following the excretion of other proteins in the plasma such as immunoglobulin. Electron microscope image and pathological analysis of kidney showed that BRCAA1 mAb Au-NCs induced some structural injury such as capillaries endotheliocyte damage, pycnosis, karyorrhexis and hyalomitome acidophilia enhancement. Biochemical indexes including ALT, AST, BUN, TBIL, CK and CREA are abnormal in the period of 2 to 48 hr after the administration. The results of Western blotting and immunohistochemisty show the downregulation of three key proteins (ZO-1, Nephrin and Podocin) indicating the influence of BRCAA1 mAb Au-NCs on the foot processes of glomerular epithelial cells and shallow intercellular junctions or slit diaphragms.